The use of legal, illegal and roll-your-own cigarettes to increasing tobacco excise taxes and comprehensive tobacco control policies: findings from the ITC Uruguay Survey. (4th March 2015) - Curti, Dardo; Shang, Ce; Ridgeway, William; Chaloupka, Frank J; Fong, Geoffrey T
Abstract : Background: Little research has been done to examine whether smokers switch to illegal or roll-your-own (RYO) cigarettes in response to a change in their relative price. Objective: This paper explores how relative prices between three cigarette forms (manufactured legal, manufactured illegal and RYO cigarettes) are associated with the choice of one form over another after controlling for covariates, including sociodemographic characteristics, smokers' exposure to antismoking messaging, health warning labels and tobacco marketing. Methods: Generalised estimating equations were employed to analyse the association between the price ratio of two different cigarette forms and the usage of one form over the other. Findings: A 10% increase in the relative price ratio of legal to RYO cigarettes is associated with a 4.6% increase in the probability of consuming RYO cigarettes over manufactured legal cigarettes (p≤0.05). In addition, more exposure to antismoking messaging is associated with a lower odds of choosing RYO cigarettes over manufactured legal cigarettes (p≤0.05). Non-significant associations exist between the manufactured illegal to legal cigarette price ratios and choosing manufactured illegal cigarettes, suggesting that smokers do not switch to manufactured illegal cigarettes as prices of legal ones increase. However, these non-significant findings may be due to lack of variation in the price ratio measures. To improve the effectiveness of increased taxes and prices in reducing smoking, policymakers need to narrow price variability in the tobacco market. Moreover, increasing antismoking messaging reduces tax avoidance in the form of switching to cheaper RYO cigarettes in Uruguay.